Multiple pulmonary spindle cell hemangiomas with IDH1 mutation in Maffucci syndrome - Fels Elliott, Daffolyn Rachael; Nataraj, Kavya; Carroll, Melissa B.; Madan, Rashna; Powers, Benjamin C. (Human Pathology Reports, 2025)
Maffucci syndrome is characterized by multiple enchondromas and vascular lesions including spindle cell hemangiomas that typically arise in cutaneous or soft tissue of the extremities. The pathogenesis involves sporadic mutations in IDH1/2 genes that occur early during embryogenesis leading to mosaicism in affected tissues. The prognosis is variable in Maffucci syndrome, and patients have an increased risk of developing malignancies. We present a rare case of multiple spindle cell hemangiomas of the lung in a 41-year-old woman with Maffucci syndrome. She was found to have numerous lung nodules that were slowly progressive on surveillance CT imaging. The radiologic differential diagnosis included diffuse neuroendocrine cell hyperplasia (DIPNECH) with multiple carcinoid tumors and pulmonary metastases. A diagnosis of spindle cell hemangiomas was made following surgical lung wedge biopsy, and PCR detected an IDH1 mutation in codon 132. Annual surveillance whole body and brain MRI showed no new or enlarging lesions one year after her lung biopsy. In conclusion, spindle cell hemangiomas are a rare cause of pulmonary nodules and may arise in the setting of Maffucci syndrome. The lungs are a common site of metastasis from malignancies associated with Maffucci syndrome, but other entities should be kept in the differential diagnosis and may require biopsy for definitive diagnosis.